2020
DOI: 10.1038/s41598-020-57491-z
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vaccine Sequences Impact V1V2 Antibody Responses: A Comparison of Two Poxvirus Prime gp120 Boost Vaccine Regimens

Abstract: Nonhuman primate studies conducted after RV144 supported the importance of non-neutralizing antibodies to V2 for protection from experimental challenge. Vaccine-elicited V2 IgG correlated with delayed SIV 9-13 and SHIV acquisition 14 , and with viremia control after SIV infection 13. Passive transfer of 830 A, a V2-specific monoclonal antibody (mAb), resulted in improved viremia control in nonhuman primates 15. Many studies have reported antiviral functions that include antibody Fc effector functions and direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…The breadth of IgG responses amongst vaccine recipients to the gp120, gp140, and V1V2 antigen panels was significantly higher at month 12.5 than month 6.5 (all P < 0.001) and also higher at month 18 than at month 12 (P < 0.001, P < 0.001, and P = 0.001, respectively) ( Fig 4), indicating that IgG envelope breadth was boosted. In addition to conformational V1V2 antibody responses, linear V2 IgG responses, a correlate of decreased HIV-1 risk in the RV144 trial [19], were also elicited in HVTN 100 [20]. IgG3 bAb response rates were significantly higher at month 6.5 than at month 12.5 for 1086.C gp120 and TV1c8.2.C gp120 (P = 0.016 and P = 0.011, with estimates and 95% CIs in S4 Table), and were similar at month 18 compared to month 12 for all 3 vaccine-matched gp120 antigens (P = 0.75, 1.00, and 0.63, with estimates and 95% CIs in S4 Table; S1 Fig) and for all 4 V1V2 antigens at all timepoints (vaccine-matched antigens shown in S1 Fig) (all P > 0.50).…”
Section: Bab Responsesmentioning
confidence: 99%
“…The breadth of IgG responses amongst vaccine recipients to the gp120, gp140, and V1V2 antigen panels was significantly higher at month 12.5 than month 6.5 (all P < 0.001) and also higher at month 18 than at month 12 (P < 0.001, P < 0.001, and P = 0.001, respectively) ( Fig 4), indicating that IgG envelope breadth was boosted. In addition to conformational V1V2 antibody responses, linear V2 IgG responses, a correlate of decreased HIV-1 risk in the RV144 trial [19], were also elicited in HVTN 100 [20]. IgG3 bAb response rates were significantly higher at month 6.5 than at month 12.5 for 1086.C gp120 and TV1c8.2.C gp120 (P = 0.016 and P = 0.011, with estimates and 95% CIs in S4 Table), and were similar at month 18 compared to month 12 for all 3 vaccine-matched gp120 antigens (P = 0.75, 1.00, and 0.63, with estimates and 95% CIs in S4 Table; S1 Fig) and for all 4 V1V2 antigens at all timepoints (vaccine-matched antigens shown in S1 Fig) (all P > 0.50).…”
Section: Bab Responsesmentioning
confidence: 99%
“…Efforts to replicate RV144 vaccine-mediated protection in South Africa using a regimen analogous to the one used in the RV144 trial but with a vaccine regimen based on clade C HIV, the HVTN702 vaccine trial, failed to protect against HIV infection (66,67). Companion phase II safety and immunogenicity vaccine trials showed that levels of anti-Env Abs induced by the clade C based vaccine regimens were as high if not higher than the levels induced by the RV144 vaccine regimen (3,62,68,69). These Abs responses were tested using cells coated with monomeric rgp120 and thus, the immune monitoring strategy preferentially detected Abs to CD4i epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…The results were compared to those of another phase I trial, HVTN 100, which investigated the subtype C ALVAC and MF59-adjuvanted gp120 regimen. The immunological profiles of the two regimens were different, and it was found that the selected vaccine inserts contributed to these differences [32]. The RV144/ HVTN 097 regimen induced greater magnitude and breadth of V2 responses than the HVTN 100/HVTN 702 regimen, but the HVTN 100/HVTN 702 regimen induced higher gp120 and ADCC responses [31].…”
Section: Viral Vector Plus Proteinmentioning
confidence: 99%
“…However, when the subtype B/E and subtype C vaccines were compared in terms of the IgG antibody response against the V1V2 loop region of the 1086C HIV envelope, a lower proportion of participants responded to the subtype C vaccine. The difference in responses between the RV144/HVTN 097 and HVTN 100/HVTN 702 regimens suggest that the choice of viral sequences inserted into prime-boost vaccine regimens influences the elicitation of V2-specific antibodies [32]. V2-specific IgG antibodies had been observed as one of the correlates of protection in the RV144 vaccine trial in Thailand.…”
Section: Viral Vector Plus Proteinmentioning
confidence: 99%